Calculation of payment of fees for wastewater discharge with pH variations - Cortes Martínez Facundo; Sánchez Cohen Ignacio; Betancourt Hernández José; Ávila Garza Claudia Mayela (Revista Mexicana de Ciencias Agrícolas, 2018)
The biological system of a wastewater treatment plant works well with a range of potential of hydrogen (pH) of 6.5 to 8.5. A neutral condition is considered a pH value of 7; however wastewater of industrial processes varies significantly. When the potential of hydrogen is greater than 10 units, the biological treatment may show inhibition, burns to workers of the installation and incompatibility with the physicochemical processes of the treatment plant. Therefore, it is advisable to control the potential of hydrogen from the same plant where it is generated. Or, cover the cost of fees at the discharge of waste water into the drainage system and municipal sewage; i.e., to pay for treatment to the authority in charge of regulating discharges of wastewater. The present research note shows the methodology to determine the non-complaint range of alkaline wastewater, and the cost of fees at the discharge of waste water into the piping system, the latter considering the legal and regulatory framework.